Design opportunities for actively targeted nanoparticle vaccines. (June 2008) - Fahmy, Tarek M; Demento, Stacey L; Caplan, Michael J; Mellman, Ira; Saltzman, W Mark
Vaccines for many infectious diseases are poorly developed or simply unavailable. There are significant technological and practical design issues that contribute to this problem; thus, a solution to the vaccine problem will require a systematic approach to test the multiple variables that are required to address each of the design challenges. Nanoparticle technology is an attractive methodology for optimizing vaccine development because design variables can be tested individually or in combination. The biology of individual components that constitute an effective vaccine is often well understood and may be integrated into particle design, affording optimal immune responses to specific pathogens. Here, we review technological variables and design parameters associated with creating modular nanoparticle vaccine systems that can be used as vectors to protect against disease. Variables, such as the material and size of the core matrix, surface modification for attaching targeting ligands and routes of administration, are discussed. Optimization of these variables is important for the development of nanoparticle-based vaccine systems against infectious diseases and cancer.